Preserving the Sundanese Language through Inclusive Environmental-Based Education at Sekolah Alam Pangandaran - Siti Tuti Alawiyah; Ahmad Mustolih (Universitas 17 Agustus 1945 Surabaya, 2026)
This study explores the role of inclusive environmental-based education in preserving the Sundanese language at Sekolah Alam Pangandaran, West Java, Indonesia. As a local language rich in cultural values and regional identity, Sundanese faces the risk of erosion due to globalization and the dominance of national and foreign languages. The research aims to investigate how integrated learning approaches—combining linguistic, cultural, and ecological elements—can support the revitalization and sustainability of the Sundanese language among young learners. This study addresses a gap in the existing literature concerning the integration of inclusive environmental-based education and regional language revitalization. While previous studies have separately examined environmental pedagogy and local language preservation, limited research has explored how nature-based inclusive schooling models function as a medium for sustaining the Sundanese language. Using a qualitative descriptive method, data were collected through interviews with educators, classroom observations, and document analysis. The study collected data from 15 interview participants (5 educators and 10 students), conducted 6 classroom observation sessions, and analyzed 8 institutional documents, resulting in 29 qualitative data sources. Findings show that the implementation of nature-based experiential learning, combined with the consistent use of Sundanese in daily communication and local cultural practices, significantly contributes to increasing students’ awareness and proficiency in the language. The inclusive aspect of the curriculum, which accommodates students of diverse backgrounds and learning needs, further reinforces a sense of belonging and cultural identity. This study underscores the potential of contextual education models in sustaining regional languages and promoting cultural resilience among future generations.